2012
DOI: 10.3102/1076998611411914
|View full text |Cite
|
Sign up to set email alerts
|

Using a Theorem by Andersen and the Dichotomous Rasch Model to Assess the Presence of Random Guessing in Multiple Choice Items

Abstract: Andersen (1995, 2002) proves a theorem relating variances of parameter estimates from samples and subsamples and shows its use as an adjunct to standard statistical analyses. The authors show an application where the theorem is central to the hypothesis tested, namely, whether random guessing to multiple choice items affects their estimates in the Rasch model. Taking random guessing to be a function of the difficulty of an item relative to the proficiency of a person, the authors describe a method for creating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 7 publications
(12 reference statements)
0
44
0
Order By: Relevance
“…Person proficiency is then estimated in relation to item difficulty. For full details see Andrich (1988) and Dunne et al (2012). The map is essentially a crude histogram with items arranged on the right, from relatively easy at the bottom, to relatively difficult at the top.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Person proficiency is then estimated in relation to item difficulty. For full details see Andrich (1988) and Dunne et al (2012). The map is essentially a crude histogram with items arranged on the right, from relatively easy at the bottom, to relatively difficult at the top.…”
Section: Resultsmentioning
confidence: 99%
“…The approach adopted here is that "guessing is a function of the difficulty of the item relative to the proficiency of the person" (Andrich, Marais & Humphry, 2011, p. 1). Andrich et al (2011) propose a strategy to "remove those responses most likely to be affected by guessing" (p. 3). These responses are removed and treated as a set of missing responses.…”
Section: Guessingmentioning
confidence: 99%
“…One important point is that these are strong assumptions that not always hold. See, for instance, Chiu and Camilli (2013), Andrich, Marais, and Humphry (2012). It will be interesting to study the implications of the use of 3PL model in scoring student responses on the Brazilian National Exam of High Education (ENEM).…”
Section: Discussionmentioning
confidence: 99%
“…The same research has shown how the bias due to guessing in MC items when analyzed by the RM can be controlled (Andrich et al., , ). The importance of controlling the bias due to guessing in large‐scale assessments has both a direct and an indirect effect.…”
mentioning
confidence: 97%